Omaha Beach on D-Day - Morvan, Jean David 1969-; Tréfouël, Séverine 1981-; Lebrun, Bernard (First Second, 2015)
Graphic story based on Robert Capa's attendance at and photographs of the Operation Neptune landing operation on June 6, 1944, (D-Day) of the Allied invasion of Normandy, with essays that detail the events of the D-Day landing
"Magnum Photos"--Cover. - Originally published by Dupuis under the title "Magnum Photos - Omaha Beach, le 6 juin 1944 - Robert Capa/Morvan+Bertail" in 2014. - "Based on an original idea by Jean-David Morvan and Clément Saccomamni"--Colophon. - Graphic story based on Robert Capa's attendance at and photographs of the Operation Neptune landing operation on June 6, 1944, (D-Day) of the Allied invasion of Normandy. Followed by his photographs and historical commentary
Keywords: Capa, Robert / 1913-1954 / Comic books, strips, etc; Geschichte 1900-2000; Photojournalists / Travel / France / Normandy / Comic books, strips, etc; Operation Neptune / Comic books, strips, etc; World War, 1939-1945 / Campaigns / France / Normandy / Comic books, strips, etc; Weltkrieg (1939-1945); Journalismus; Zweiter Weltkrieg; Fotografie; Normandy (France) / History, Military / 20th century / Comic books, strips, etc; Frankreich; Comic; Bildband; Jugendsachbuch